Carcinopodacarus polymorphus gen. n. et sp n. from Guira guira (Cuculiformes: Cuculidae) in Brazil: a first example of male polymorphism in the family Dermationidae (Acariformes: Analgoidea) - Hernandes, Fabio Akashi [UNESP]; Pedroso, Luiz Gustavo A. [UNESP]; Bochkov, Andre V. (Folia Parasitologica, 2015)
Carcinopodacarus polymorphus gen. n. et sp. n. (Acariformes: Dermationidae: Dermationinae) is described from the guira cuckoo Guira guira (Gmelin) (Cuculiformes: Cuculidae) in Brazil. The new genus differs from the closest genus, Psittophagoides Fain, 1964, by the following features: in both sexes, the anterior spines of trochanters I and II are absent (vs present in Psittophagoides), setae d2 are distinctly developed (vs only alveoli), and genual setae mGI are absent (vs present); in males, the hysteronotal shield is split transversally at the level of trochanters III (vs hysteronotal shield entire); in females, the platelets situated posterior to the propodonotal shield are absent (vs present), the metapodosomal sclerites are present (vs absent), and the adanal shields are fused anteriorly to each other (vs separated from each other). In this species, andropolymorphism is detected for the first time for the family. It involves various characters but the most impressive feature is the structure of legs III. In hetero-and mesomorphic males, these legs are strongly hypertrophied and have a distinct ventral spur on femora III; in homeomorphic males, legs III are not modified and subequal to legs IV.
Keywords: Acari; andropolymorphism; cuculiform birds; parasites; Psoroptidia; systematics